Cancer incidence, mortality, and survivorship in African women: a comparative analysis (2016-2020) - Chibuikem Chrysogonus Nwagwu; Uchenna Petronilla Ogoke (Frontiers Media S.A., 2024)
ObjectivesThis research aims to provide concrete insight into cancer incidence, mortality, and survivorship dynamics among African women between 2016 and 2020.MethodsThe study computes the Mortality-to-Incidence Ratio (MIR) for 53 countries in Africa with available mortality and incidence data. It uses relevant Life Tables to obtain the 5-year Relative Survival rate for women in different age cohorts based on General Survival Rate and 5-year Cancer Prevalence data from the World Health Organization (WHO). The study performs an analysis of variance tests.ResultsThe results of the initial data analysis show that women in the top economies in Africa have the highest cancer incidence and mortality. The study also finds that women in Northern and Southern African countries have higher relative survival rates and lower MIR than other African regions. ANOVA results confirm statistically significant differences in 5-year relative survival across the African regions. The relative survival at 5 years was an average of 45% across all age groups within the continent although relative survival is highest among females aged 5-19 and 80-84. The lowest relative survival rates are seen for infants (0-4), adolescents and young adults (25-29), and the very elderly (85+).ConclusionThe study concludes that while cancer incidence in Africa is linked to affluence, survival is very challenging, especially for the least developed economies in Western, Eastern, and Central Africa. The results indicate the need for crucial intervention in the continent concerning awareness, research, and data collection methodology.